The Odyssey - Williams, Lara (Writer of Treats) (Zando, 2022)
"Ingrid works on a gargantuan cruise ship where she spends her days reorganizing the gift shop shelves and waiting for long-term guests to drop dead in the aisles. On her days off, she disembarks from the ship, wasting the hours aimlessly following tourists around, drinking the local alcohol, and buying clothes she never intends to wear. It's not a bad life. At least it distracts her from thinking about the other life--the other person--she left behind five years ago. That is, until the day she is selected by the ship's enigmatic captain and (ill-informed) wabi-sabi devotee, Keith, for his mysterious mentorship program. Encouraging her to reflect on past mistakes and her desperation to remain lost at sea, Keith pushes Ingrid further than she ever thought possible. But as her friendships and professional life onboard steadily fall apart, Ingrid must ask herself: how do you know when you have gone too far?" --